2020
DOI: 10.2147/copd.s266021
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Predictive Value of microRNA-134 and microRNA-1233 for the Early Diagnosis of Acute Exacerbation of Chronic Obstructive Pulmonary Disease with Acute Pulmonary Embolism</p>

Abstract: Background: The differential diagnosis of acute exacerbation of chronic obstructive pulmonary disease (AECOPD) with acute pulmonary embolism (APE) complications are difficult because of the variability of clinical presentations and the shortage of an unfailing screening biomarkers or instruments. Objective: Aimed to detect and compare the expression of serum microRNAs (miR-1233, miR-134) in AECOPD patients complicated with APE. Patients/Methods: Blood samples were collected from 52 AECOPD patients (13 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…As expected, TNF-α treatment increased the mRNA and protein level of MUC5AC in 16HBE cells 1D,E). The previous studies have demonstrated that miR-134-5p (miR-134) and miR-146a-5p (miR-146a) are involved in mucus hypersecretion in COPD (12,(16)(17)(18)(19). To explore the association of TNF-α-induced MUC5AC expression with these miRNAs, we first assessed whether TNF-α regulated the expression of these miRNAs.…”
Section: Tnf-α Treatment Increased Muc5ac Expression and Repressed Mir-134-5p (Mir-134) And Mir-146a-5p (Mir-146a) Expression In 16hbe Cementioning
confidence: 99%
See 1 more Smart Citation
“…As expected, TNF-α treatment increased the mRNA and protein level of MUC5AC in 16HBE cells 1D,E). The previous studies have demonstrated that miR-134-5p (miR-134) and miR-146a-5p (miR-146a) are involved in mucus hypersecretion in COPD (12,(16)(17)(18)(19). To explore the association of TNF-α-induced MUC5AC expression with these miRNAs, we first assessed whether TNF-α regulated the expression of these miRNAs.…”
Section: Tnf-α Treatment Increased Muc5ac Expression and Repressed Mir-134-5p (Mir-134) And Mir-146a-5p (Mir-146a) Expression In 16hbe Cementioning
confidence: 99%
“…Out of the 20 miRNAs, miR-134-5p and miR-146a-5p are lower expressed in COPD patients, and are crucial miRNAs associated with several mucus hypersecretion-correlated potential targets (12). miR-134-5p is a potential marker for the clinical diagnose of acute exacerbation of COPD (16). Down-regulated miR-146a-5p is involved in the pathogenesis of COPD through inducing more proinflammatory phenotype (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…D-dimer is a classic biomarker for detecting and evaluating PE progression. Of interest, the areas under the curves (AUCs) for the correlation of miR-134 and miR-1233 with PE progression were 0.931 (95% confidence interval [CI] 0.863–0.999) and 0.884 (95% CI 0.79–0.978), respectively, which were higher than those of D-dimer (0.628) (95% CI 0.447–0.809) and Wells score (0.577) (95% CI 0.389–0.765) ( Peng et al, 2020 ). This study provided evidence that the levels of serum miR-1233 and miR-134 are significantly upregulated in COPD patients with APE complication.…”
Section: Mirnas As Pe Biomarkersmentioning
confidence: 98%
“…59 Latest data identified circulating miR-1233 as a sensitive and specific biomarker for the early diagnosis of APE. 60 The above-mentioned differential expression experiments of miRNAs by quantitative reverse transcription polymerase chain reaction (qRT-PCR) indicate that miRNAs can be successfully used in the diagnosis of PE.…”
Section: Micrornasmentioning
confidence: 99%